0127 Self reported confidence increases after simulated endovenous therapy course. (2nd November 2015) - Bamford, Richard; Chinai, Natasha; Coulston, James; Stewart, Andrew
Abstract : Background: Endovenous therapy is a rapidly developing and important field in vascular surgery and requires a unique skill set. Limitations on trainee time and access to endovenous procedures limits the opportunities trainees have to develop these specialist skills and understanding. The aim of this study is to identify how effective simulators can be in allowing trainees to develop these areas. Method: All vascular trainees within a training region were invited to attend an endovenous training day using phantom limb simulators. Trainees were asked to complete a pre and post course assessment of their experience, confidence and understanding of the knowledge and technical skills required to perform endovenous treatments. Results: Seventy five per cent (6/8) of vascular trainees within the region attended the course. Of those, none had been involved in more than 30 endovenous cases and two had been involved in more than 20. Self-reported confidence significantly improved across all skills assessed on the day. These included identifying venous structures with ultrasound (p = 0.0006), ultrasound guided venous access (p = 0.0001), ultrasound guided venous catheter placement (p = 0.001) and ultrasound guided tumescence placement (p = 0.0009). Trainees reported an increased understanding of the procedural steps involved with endovenous laser treatment (p = 0.0001) and radiofrequency ablation techniques (p = 0.0002). All trainees agreed or strongly agreed to have a better understanding of how foam sclerotherapy, laser therapy and radiofrequency ablation worked and the indication for its use. Conclusion: These data suggest that a structured course using phantom limb simulators improves trainees' confidence and may be a useful adjunct for novice vascular trainees to develop skills and understanding in endovenous therapy. Reference: Brittenden J, Cotton SC, et al . Clinical effectiveness and cost-effectiveness of foam sclerotherapy, endovenouslaser ablation and surgery for varicose veins: results from the comparison of LAser, Surgery and foam Sclerotherapy (CLASS) randomised controlled trial. Health Technol Assess. 2015;19(27):1–341